Структура и межпоколенная динамика жизненных притязаний молодежи в России и Украине: 1985–2001 - Магун, В.; Энговатов, М. (Социология: теория, методы, маркетинг, 2004)
The article deals with dynamics of life claims among several generations of Russian and Ukrainian young people during revolutionary changes in countries of the former USSR of 1985-2001. The research revealed the tendency of rising claims, characteristic of the second part of 1980-ies, which did not change in 1990-1995, but in 1995-2001 it tended to go down although they still exceeded the level of 1985. The first jump in expectations, related to new opportunities appeared under conditions of transformation, was burdened by understanding of barriers that existed on the way to individual aims and goals of society as a whole.